Compendium of texts with professional approach in the subject Spanish - Literature of the trade schools Julio Antonio Mella of Holguin. Cuba - Pérez Martínez, Lisandra; Zaragoza Morales, Nurbia Ivia; Cruz Cabezas, Miguel Alejandro; Corona Soria, Amarilis (Revista Científica Estelí, 2022)
In the teaching-learning process of Spanish - Literature of the trade school it is fundamental the use of texts with professional character, so that students acquire knowledge, develop skills, professional values, interests, positive attitudes towards the trade in which they are prepared in accordance with the demands and standards of professional performance established by the jobs. However, in a diagnosis carried out in the Julio Antonio Mella profession school in Holguin, it was found that there are insufficiencies in this process that affect the students' performance. This article arises from the need to contribute to the learning of the students of the School of Professions in the subject Spanish - Literature. Theoretical, empirical and mathematical-statistical methods were used to design the proposed compendium. The authors propose a compendium containing texts with professional approach and the procedure for its use, to favor the development of the professional teaching-learning process of the subject Spanish - Literature in the Julio Antonio Mella School of Professions in Holguin. The results correspond to the master's thesis of the main author.